2009
DOI: 10.1590/s0066-782x2009001200019
|View full text |Cite
|
Sign up to set email alerts
|

Frequência etiológica da hipertensão pulmonar em ambulatório de referência na Bahia

Abstract: Background: Pulmonary hypertension (PH) results from several etiologies, with possible geographic influences; however, few studies have described the etiological frequency of PH, especially in our country. It is not clear whether there is an association between etiology and pulmonary pressure level or symptom intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Clinical studies in SchPAH are scarce and restricted to a few PH centers in the world, largely in Brazil (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). Additionally, most of the clinical data reported to date were generated in centers situated in non-endemic areas for schistosomiasis (62,64,65,(67)(68)(69).The classic comparator disease for SchPAH is IPAH, which occurs worldwide and has been much more widely studied despite a much lower disease burden (the incidence is approximately 1 case/million individuals/year) (77).…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 99%
“…Clinical studies in SchPAH are scarce and restricted to a few PH centers in the world, largely in Brazil (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). Additionally, most of the clinical data reported to date were generated in centers situated in non-endemic areas for schistosomiasis (62,64,65,(67)(68)(69).The classic comparator disease for SchPAH is IPAH, which occurs worldwide and has been much more widely studied despite a much lower disease burden (the incidence is approximately 1 case/million individuals/year) (77).…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 99%
“…The prevalence of elevated pulmonary pressures in patients with schistosomiasis is still controversial, but it has been reported as one of the most important etiologies of PAH 1-5,24,25 . This is the first study to assess the influence of gender on echocardiography-derived SPAP and to investigate the role of menopausal status and pregnancy history among patients diagnosed with SPAH.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, there are about 60,000 cases (Brito, 2017). A study in a reference outpatient clinic in Bahia identified the prevalence of idiopathic pulmonary arterial hypertension, followed by PH caused by schistosomiasis (Machado, et al, 2009); another carried out in two reference centers in São Paulo presented the same results, in addition to being associated with connective tissue diseases in 10% of the cases (Lapa et al, 2006). Studies reveal that PH occurs from the third decade of life in women, while in men the disease usually occurs from the age of forty (Health Care Secretariat, 2014).…”
Section: Pulmonary Hypertension Affects 25 Million People Worldwide (...mentioning
confidence: 93%